A filtration model for prediction of local flux distribution and optimization of submerged hollow fiber membrane module. Issue 12 (26th July 2015) - Li, Xianhui; Li, Jianxin; Wang, Hong; Huang, Xiaoxu; He, Benqiao; Yao, Yonghong; Wang, Jie; Zhang, Hongwei; Ngo, Huu Hao; Guo, Wenshan
Abstract : A filtration mathematical model was developed on the basis of complete mass balance and momentum balance for the local flux distribution prediction and optimization of submerged hollow fiber membrane module. In this model, the effect of radial permeate flow on internal flow resistance was considered through a slip parameter obtained from the local flux experiments. The effects of fiber length, inside diameter, and average operating flux on local flux distribution were investigated using this model. The predicted results were in good agreement with the experimental data obtained from literature. It was also found that the asymmetry distribution of local flux could be intensified with the increase of average operating flux and fiber length, but slowed down with the increase of fiber inside diameter. Furthermore, the simulation coupled with energy consumption analysis could efficiently predict and illustrate the relationship between fiber geometry and water production efficiency. © 2015 American Institute of Chemical Engineers AIChE J, 61: 4377–4386, 2015